Scientific research in computer science - Arwa Alyasiry; Hadeel Al Ubaidy (Cybrarians Journal, 2007)
This paper displays the importance of selection research objective and supervisor; In addition this paper suggested the optimal research methods that help researcher to get to optimal results in efficient way. This paper shows the thesis writing style and arrangement in way that to be readable for reader about reality of type and size of the work. The one important result of this paper it's the successful of scientific research must depend about many features that join together and miss one of the research methods that mean unsuccessful research.